2000
DOI: 10.1046/j.1365-2249.2000.01164.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HLA-DR, costimulatory molecules B7-1, B7-2, intercellular adhesion molecule-1 (ICAM-1) and Fas ligand (FasL) on gastric epithelial cells inHelicobacter pylorigastritis; influence ofH. pylorieradication

Abstract: SUMMARYThere is evidence that Helicobacter pylori infection up-regulates the expression of HLA class II molecules by gastric epithelial cells (GEC). In this study we evaluated whether GEC are capable of expression of costimulatory molecules in H. pylori gastritis. The expression of FasL by GEC, before and after eradication of H. pylori, was also studied. Thirty patients (23 men) aged 27±81 years (53´67^13´99 years (mean^s.d.)) with dyspepsia were studied. Upper gastrointestinal endoscopy was performed and six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 61 publications
1
23
0
Order By: Relevance
“…This differential expression of Fas Ag and MHCII within the gastric mucosa creates the potential for receptor interaction and variable signaling outcomes. MHCII is expressed in metaplastic and dysplastic tissue (unpublished observation) as well as in carcinoma (1,7,48), making a scenario of MHCII/Fas Ag receptor interaction plausible.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This differential expression of Fas Ag and MHCII within the gastric mucosa creates the potential for receptor interaction and variable signaling outcomes. MHCII is expressed in metaplastic and dysplastic tissue (unpublished observation) as well as in carcinoma (1,7,48), making a scenario of MHCII/Fas Ag receptor interaction plausible.…”
Section: Discussionmentioning
confidence: 95%
“…During Helicobacter infection, gastric mucosal cells upregulate surface MHCII expression and costimulatory molecules (1,15,16,53) and have the ability to weakly present antigens (1,47). Additionally, there is evidence that Helicobacter pylori may bind the gastric cell via the MHCII complex and regulate apoptotic responses (15).…”
mentioning
confidence: 99%
“…Therefore, there is some uncertainty about the location where priming of the immune response to H. pylori occurs. Gastric epithelial cells up-regulate expression of major histocompatibility complex (MHC) class II and costimulatory molecules during H. pylori infection (17,255), and potentially these cells have a role in antigen presentation. Monocytes, macrophages, and dendritic cells in the lamina propria of the gastric mucosa also may play important roles in antigen presentation (115,222,240).…”
Section: Chronic Infectionmentioning
confidence: 99%
“…Several studies have demonstrated the overexpression of HLA class II molecules in gastric mucosa [140,141,142,143,144,145,146] and circulating mononuclear cells [147] in patients with gastric inflammation. It has been reported that gastric epithelial cells as well as classical APCs such as macrophages express HLA-DR, -DP, and -DQ [141,142,143,144], and that the extent of epithelial HLA-DR expression is parallel with the degree of inflammation [141, 146] and activity [146].…”
Section: Immunitymentioning
confidence: 99%
“…It has been reported that gastric epithelial cells as well as classical APCs such as macrophages express HLA-DR, -DP, and -DQ [141,142,143,144], and that the extent of epithelial HLA-DR expression is parallel with the degree of inflammation [141, 146] and activity [146]. On the other hand, the expression of HLA-DR was not increased in the lamina propria of gastric mucosa infected with H. pylori [144].…”
Section: Immunitymentioning
confidence: 99%